Retinopathy of prematurity in the United Kingdom: retreatment rates, visual and structural 1-year outcomes. (November 2018) - Adams, Gillian; Bunce, Catey; Xing, Wen; Butler, Lucilla; Long, Vernon; Reddy, Aravind; Dahlmann-Noor, Annegret
Abstract Aims To evaluate retreatment rates, visual and anatomical outcomes at 1-year postnatal age in infants treated for retinopathy of prematurity (ROP) Methods Longitudinal national surveillance study of infants treated for ROP in the United Kingdom between December 2013 and December 2014, supported by the British Ophthalmic Surveillance Unit. Here we report retreatment rates, anatomical, visual and refractive outcomes at 1-year follow-up. Results One-year follow-up forms were completed for 168 children of the original cohort of 327 (51.4%). Twenty-two had at least one retreatment: 17/153 right eyes (REs, 11.1%) after initial diode laser, and 5/14 REs (35.7%) after initial injection of anti-vascular endothelial growth factor (VEGF) antibody. Median (interquartile range) RE best-corrected visual acuity was 0.6 (0.4–1.0) (n  = 46 REs), and median acuity both eyes open 0.4 (0.3–0.7) logMAR (n  = 89). Median spherical equivalent (RE) was 0.44 (−1.3 to 1.3) dioptre (D) (n  = 116). Median astigmatism (RE) was 0.5 (0–1.0) D (n  = 111), and median anisometropia 0.125 (0–0.75) D (n  = 116). Twenty-four children (20.5%) had been prescribed glasses. Sight impairment certification eligibility information was available for 131 children: 11 (8.4%) were eligible to be certified as sight impaired, and 5 (3.8%) as severely sight impaired. Conclusions Retreatment rates are in line with previous reports, and appear higher after initial anti-VEGF antibody than after initial diode laser. Refractive outcomes are in line with previous studies, with a trend towards early emmetropia and myopia following diode laser, particularly in more severe ROP.